Pola Komunikasi Penyuluhan Pertanian Lapangan (PPL) pada Kelompok Tani Karya Baru di Desa Suanae Kecamatan Miomaffo Barat Kabupaten Timor Tengah Utara - Duan, Margaretha Cosmos Lein; Matoneng, Ody Wolfrit; Falo, Marsianus; Mambur, Yohanes Pebrian Vianney (AGRIMOR, 2024)
This research focuses on communication patterns, especially communication built within the Karya Baru farmer group to support farming and the development of the farmer group. The aim of this research is to find out the description of the internal and external factors of farmers in the Karya Baru farmer group, to know the picture of field agricultural extension (PPL) communication in the Karya Baru farmer group, and to find out what factors influence field agricultural extension (PPL) communication in the Karya Baru farmer group. The methods used in this research are mixed methods. Determining informants used the purposive sampling method with the technique of taking respondents by census (saturated sampling). The population and sample in this study used a purposive sampling technique, namely all members of the "Karya Baru" farmer group in Suanae Village, West Miomaffo District, North Central Timor Regency, with 23 members. Data collection was carried out using survey methods, observation, and data collection using questionnaires given directly to respondents. The results of this study state that the characteristics of respondents are internal factors that have a real influence on communication patterns, namely length of farming and cosmopolitan, while external factors, namely the role of farmer groups and agricultural extension methods, have a real influence on communication, namely the individual approach and group approach, which also have a real influence on communication.